Identification of Persister Drug Combination Clinafloxacin + Cefuroxime + Gentamicin That Eradicates Persistent Pseudomonas aeruginosa Infection in a Murine Cystic Fibrosis Model. Issue 1 (27th March 2023) - Yuan, Yuting; Yee, Rebecca; Gour, Naina; Dong, Xinzhong; Feng, Jie; Shi, Wanliang; Zhang, Ying
Abstract: Pseudomonas aeruginosa can cause persistent infections, such as biofilm infections, in cystic fibrosis patients, which are difficult to cure due to non-growing persister bacteria that are not effectively killed by the current treatments. While antibiotic activity against growing P . aeruginosa is well documented, their activity against non-growing stationary phase cultures is less clear. Here, we evaluated six major classes of antibiotics, including cell wall and cell membrane inhibitors, protein synthesis inhibitors, DNA synthesis inhibitors, RNA synthesis inhibitors, sulfa drugs and nitrofurantoin, for their activity against growing and non-growing P. aeruginosa . We found that cell wall and cell membrane inhibitors (cefuroxime and colistin), DNA synthesis inhibitors (clinafloxacin) and sulfa drugs (sulfamethoxazole) had good activity against stationary-phase bacteria, while protein synthesis inhibitors (gentamicin), RNA synthesis inhibitor (rifampin) and nitrofurantoin showed relatively poor activity. Clinafloxacin was the only drug able to completely eradicate stationary-phase bacteria within four days. The cefuroxime + gentamicin + clinafloxacin combination was able to kill all bacteria from a biofilm within two days, whereas the clinically used drug combination cefuroxime + gentamicin/colistin only partially killed the biofilm bacteria. In a murine persistent cystic fibrosis lung infection model, only the cefuroxime + gentamicin + clinafloxacin drug combination eradicated all bacteria from the lungs, whereas clinafloxacin alone, cefuroxime + clinafloxacin or the currently recommended drug combination cefuroxime + gentamicin failed to do so. The complete eradication is a property of the clinafloxacin combination, as the otherwise identical levofloxacin combination did not clear the bacterial loads from the lungs. Our findings offer new therapeutic options for more effective treatment of persistent P . aeruginosa infections, with possible implications for treating other persistent infections.